Strategies for strengthening employee performance at LPPL agropolitan television to support sustainable tourism in Batu City - Lestari, Pudji; Ajisaputra, Arnanda; Wardani, Made Iska Aprilita; Soesetyo, R. Himawan Arif (Priviet Social Sciences Journal, 2025)
This study aims to analyze the factors contributing to the improvement of employee performance at the Local Public Broadcasting Institution (LPPL) Agropolitan Television, Batu Tourism City, East Java. This study focuses on the influence of interpersonal communication and workplace comfort on employee performance. A quantitative associative approach was employed to provide a comprehensive understanding of employee performance optimization at the LPPL Agropolitan Television. Respondents were selected using a saturated sampling method, involving all 40 employees whose performances were assessed. Data was analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The findings reveal that workplace comfort directly enhances employee performance, whereas interpersonal communication improves performance only when it first fosters workplace comfort. Furthermore, workplace comfort fully mediated the relationship between interpersonal communication and employee performance. It is recommended that the leadership of LPPL ATV and the Department of Communication and Information of Batu Tourism City continue to provide adequate facilities to create a comfortable working environment. Such efforts are essential to improving employee performance in alignment with the shared vision and mission of advancing sustainable tourism in the Greater Malang area.